Design and Construction of Heart Beat Sensor Using Arduino - Mahmood, Ayat Fawaz Ghazi; Abdulrazzaq Hasan, Zainab Muayad; Hashim Hamza, Zahraa Kadhum; Abdalzahra, Furqan Firas Jasim (Journal of Science in Medicine and Life, 2025)
This project addresses the methodology for real-time monitoring of a patient's heart rate. The proposed system utilizes a sensor that detects the heartbeat, which is managed by a microcontroller. The heartbeat readings are presented on an LCD monitor. The heartbeat sensor is employed to capture the heartbeat over a designated time period and calculates the beats per minute. The primary aim is to continuously monitor the patient's heart rate, which should be accessible to the attending physician. In hospital settings, patient health monitoring is conducted by healthcare staff, who consistently check and maintain records of the patient's heart rate. The essential components of this system comprise a power supply, an Atmega328 microcontroller, a heartbeat sensor, and an LCD display.